A System Dynamics Tool for Higher Education Funding and Quality Policy Analysis - Oyo, Benedict; Williams, Ddembe; Barendsen, Erik (International Conference of the System Dynamics Society, 2008)
Conceptually, the level of funding of higher education activities is directly proportional to its strategic directions/implementations and hence quality. In developing countries, these dependencies are far from straightforward due to ad-hoc reactions to reduced funding. This paper contributes to the development of tools for this management challenge. We investigate the dynamics of higher education funding and ensuing impact on part-time teaching, staff to student ratios, staff development, research productivity, and hence the perceived quality, using a system dynamics simulation model. The model developed is based on higher education literature in the developing world in general and Uganda in particular. We use the resulting model to review policies on funding and quality in higher education, and ultimately envisage that the model can easily be adapted to higher education in other environments.
Keywords: System dynamics; Higher education; Funding; Quality; Model